DOZ047.84: Use of a decannulation protocol in the pediatric population: decrease in the day of use. (24th June 2019) - Urquizo, M; Canepari, A; Ricciardelli, M; Sanchez, M
Abstract: Objective: This study aimed to compare days of use of a tracheostomy cannula in two groups of patients: one group used a guided decannulation protocol carried out by an interdisciplinary team and the other group did not apply any protocol. Design and Population: A comparative retrospective cohort study of 40 patients was carried out, of whom 20 were decannulated without a protocol (WOP) between 2008 and 2011 and in the other 20 patients, the decannulation protocol (WP) was applied by an interdisciplinary team between 2015 and 2017. Method: In 2015 a guided decannulation evaluation protocol was implemented in patients successfully weaned from prolonged mechanical ventilation that consisted of three parts: (1) daily evaluation tracheotomy requirement; (2) measuring subglottic pressure, decreasing the internal diameter of the cannula and usage of phonation valve; and (3) endoscopic evaluation, occlusion test according to age, and decannulation. The main variable was days of use of tracheostomy cannula in both groups, from the day of the surgery to the day of decannulation. Results: In the cohort WOP of the 38 tracheotomized children, 20 achieved decannulation. In the group WP, the first 20 children who reached decannulation were consecutively enrolled, out of a total of 24 tracheotomized patients in that period. The median age was 58 months, with IQR (21.5–138); the diagnoses of admissions for both groups were of respiratory cause 20% CI 95% (10–35), cardiovascular 15% CI 95% (7–30), neurological 17.5% CI 95% (8–33), and other 47.5% CI 95% (32–63). The surgical procedure of tracheostomy, 52.5% were percutaneous with 95% CI (37-68) while 47.5% were surgical with 95% CI (32–63). The median use of the tracheostomy cannula was 46 days with an IQR (29–144). When analyzing the days of cannulation in both cohorts, a median of 94 days WP and CI 95% (51–261) in the group WOP and a median of 33 days WP and CI 95.5% (23–44) were found, obtaining a value of Wilcoxon–Mann–Whitney p 0.0012. Conclusions: The use of a decannulation protocol applied by an interdisciplinary work team showed a significant decrease in days of use of tracheostomy cannulas in pediatric patients unrelated from the respiratory assistance.